Pengaruh Karakteristik Wirausaha Terhadap Keberhasilan Usaha Batu Bata Di Desa Tangkit Kecamatan Sungai Gelam Kabupaten Muaro Jambi - Febriana Junita (Jurnal Dinamika Manajemen, 2020)
The purpose of this study was to determine the effect of entrepreneurial characteristics on the success of brick-making entrepreneurs in Tangkit Village, Sungai Gelam District, Muaro Jambi Regency. The population in this research is the brick entrepreneur in Tangkit Village. The sampling method in this study was using the census technique as many as 41 people. Data were collected using a questionnaire that has been tested for validity and reliability. The data analysis method used multiple linear regression analysis. The results showed that there was an influence between the characteristics of entrepreneurship on the success of bricks entrepreneurship both simultaneously and partially. Entrepreneurial characteristics have an effect of 50.3%, the remaining 49.7% are influenced by other variables not examined in this study. The conclusion of this study is that there is a significant positive influence between entrepreneurial characteristics (self-confidence, risk taking and leadership) on the success of the brick business in Tangkit Village.